IMPACT OF JABAL KELOR DEVELOPMENT AS A TOURISM ATTRACTION - Steviani Batti; Dhimas Setyo Nugroho; Andi Lopa Ginting; Herry Novrianda (JELAJAH: Journal of Tourism and Hospitality, 2019)
Jabal Kelor tourism development has triggered a positive impact on the residents of the Dadap Kulon hamlet. The purpose of this study is to present an analysis of the impact of community-based tourism development in Jabal Kelor. In this study, semi-structured interviews were conducted with key informants involved in developing Jabal Kelor. Observation and documentation to check the validity of the data. Interactive data analysis techniques take place continuously until complete until the data is saturated. The results showed that the Dadap Kulon community felt a positive impact on the development of Jabal Kelor as a tourist attraction. The positive impact can be seen from the economic, environmental, social, and political aspects. Namely, the emergence of new jobs increased income and allocation of funds for tourism development. Regional carrying capacity and waste disposal management. Improvement of the quality of life and pride of the community. Activating community participation and building a management system.